Estudio del impacto económico en la implementación de las cocinas de inducción de la ciudad de Quito provincia de pichincha en el período 2014-2015. - Maita Sotomayor, Jonathan Iván (2017)
The present study is based on the need to quantify the economic impact generated by the implementation of induction cookers in the city of Quito, using the type of exploratory research of reliable sources in web pages, scientific articles, books, related journals, field, data were collected from primary sources, these being the homes of the neighborhoods of Quito and the descriptive establishing a situational diagnosis on the use of LPG gas and the use of induction cookers, through qualitative and quantitative methods that have allowed to obtain results as : consumption kwh, ratio of income vs cost of cooking to induction, cost-benefit ratio in investment. The analysis of these indicators show us that the best option is the change of LPG cookers by induction cookers.